Hubungan antara Dukungan Orang Tua dengan Prestasi Belajar Siswa Kelas Tinggi SDN 243 Ujung Salangketo Kecamatan Mare Kabupaten Bone - Adnan K Adnan K; Muhammad Amin; Filda Niar (Universtas Negeri Makassar, 2022)
The problem in this study is the lack of parental support to students, so that student learning achievement decreases. This study is a quantitative study with a correlation design that aims to determine the relationship between parental support and learning achievement of high-grade students of SDN 243 Ujung Salangketo, Mare District, Bone Regency. The results showed that there was a significant relationship between parental support and the learning achievement of high-grade students of SDN 243 Ujung Salangketo, Mare District, Bone Regency with a calculated value of 5.7773 greater (>) a ttabel value of 1.66600 which means that H0 was rejected and H1 was accepted. Based on data analysis, it can be concluded that parental support will have an impact on student learning achievement. From these conclusions, the impact resulting from this study is known that good parental support will increase student learning achievement.